Good Faith in Plantation Management Contract between PTPN V and Koperasi Nenek Eno Senamanenek - Firdaus Firdaus; Ulfia Hasanah; Samariadi Samariadi (Faculty of Law, Maranatha Christian University, 2023)
Good faith is fundamentals in every contract, without which a contract will find it difficult to achieve its goals. In 2019, through a contract made before a notary in the hall of Kampar Regent Office, Kooperasi Nenek Eno Senamanenek and PT. Perkebunan Nusantara IV start a new beginning after a long period of dispute over Senamanenek community’s customary land. The good faith in fulfillment of contract between KNES and PTPN V would affect the legal relationship between these two parties. For KNES, the realization of the clauses within the contract will affect senamanenek community who become the member of the cooperative. The contract object was a palm oil plantation owned by the cooperative member. This empirical legal study scrutinized the implementation of good faith in the contract between KNES and PTPN V By identifying the law and the effectiveness of legal principles in the community. It took place in Kampar Regency. Primary, secondary, and tertiary data were collected through interviews and literature review. This study concludes that the good faith has not been fully implemented in the contract between PTPN V and KNES due to legal and non-legal factors. Therefore, both parties are suggested to possess a good faith in all stages of the contract-making process, from the pre-contract, contract, and post-contract stages. They are also suggested to minimize factors inhibiting good faith in the contract.